The impact of knowledge management in pair programming on program quality - Ahmad, Mazida; Abd Razak, Ainul Husna; Omar, Mazni; Yasin, Azman; Romli, Rohaida; Abdul Mutalib, Ariffin; Zahari, Ana Syafiqah (Springer International Publishing, 2015)
This paper reports on an initiative that determines the most appropriate technique for supporting students’ programming ability.The proposed technique combines pair programming (PP) and SECI process that is a knowledge management (KM) model. Combining PP and SECI resulted in the formation of four approaches, which are named as NSNR, NSYR, YSNR, and YSYR. In those four approaches, the subjects who are students of IT-related programs in a higher learning institution complete a set of programming questions. The approaches were then compared based on the subjects’ scores in their program codes. Descriptive statistics was used to analyze the gathered data. Generally, the results show that switching the roles (driver and navigator) in PP enhances good quality of coding. Through this study, an initial formation of the KM model and programming technique is contributed in enhancing program quality. Further, future work to be considered can be a rigorous theoretical formation for constructing other important determinants to enhance program quality because the findings of this research are minimal to SECI model and pair programming technique only.